Growth temperature and UVB radiation stress responses in Metarhizium anisopliae strain CPMa1502 (2019)
The oil palm is an economically important crop due to its high productivity and broad industrial applicability (Sabate 2016). In Colombia, this crop is grown in di erent agro-ecological zones (Borrerio 2018) where the environmental conditions are favorable to several insect pests. One of the most economically important pests is the fruit scraper Demotispa neivai (Bondar, 1940) (Coleoptera: Chrysomelidae) (Aldana et al. 2004). To control this pest, CENIPALMA isolated in Colombia (Barrancabermeja), and selected the strain of Metarhizium anisopliae CPMa1502 as a new active principle for biological control because it showed the highest mortality on adults of D. neivai (87.7%) on laboratory conditions (Aldana et al. 2004, Bustillo, 2014; Montes et al. 2016). Temperature and UVB radiation are factors that can a ect the mass production and biocontrol activity of the fungus. The evaluation of its in uence is an important part of the development of a future bioproduct. This work evaluated the conidia tolerance to di erent stress conditions of temperature (20, 25, 30, 35°C) and several exposure times of UVB radiation, measuring conidial vigor and germination, cellular viability, and radial growth rate.